Fe2O3 nanotube / zinc ferrite open nanocage superstructure composite material as well as preparation method and application thereof
The preparation of Fe2O3 nanotube/ZnFe2O4 open nanocage superstructure composite material through self-template epitaxial growth strategy and heat treatment process, solving the problem of insufficient gas sensitivity performance of the existing Fe2O3 nanostructure in gas sensors, and achieving high sensitivity response to hydrogen sulfide gas and good stability.
Patent Information
- Application Number
- CN202411893043.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-20
AI Technical Summary
There is still room for improvement in the gas sensitivity performance of the existing Fe2O3 nanostructures in gas sensors, especially in terms of operating temperature, detection limit, response/recovery time and stability.
The self-template epitaxial growth strategy combined with heat treatment technology was used to prepare Fe2O3 nanotubes/ZnFe2O4 open nanocage superstructure composite material, and the nanomaterials with hierarchical open structure were controlled through this method.
A high sensitivity response to hydrogen sulfide gas is achieved, with relatively low operating temperature, low detection limit, fast response/recovery time, good reversibility and long-term stability, and the selectivity to H2S is significantly better than other reducing gases.
Smart Images

Figure CN119750654A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a Fe2O3 nanotube / zinc ferrite open nanocage superstructure composite material and a preparation method and application thereof. Background Art
[0002] In daily life, gas sensors have been applied in various fields such as environmental monitoring, medical diagnosis, and agriculture. Gas sensors based on semiconductor metal oxides have attracted great interest in the past few decades due to their high performance and adjustable performance, simple structure, convenient manufacturing, and intuitive sensing mechanism. Although people have made efforts to introduce some new gas-sensitive materials in the field of sensing, traditional metal oxides are still universal and effective sensing materials.
[0003] As a classic n-type semiconductor material with a band gap of 2.1 eV, Fe2O3 has been widely used in biomedicine, cancer targeted therapy, lithium-ion batteries, organic pollutant degradation, catalysis, gas sensors and other fields due to its abundant resources, high conductivity and good stability. It is well known that the gas sensing performance of metal oxides depends largely on their morphology, such as aspect ratio, size, crystal plane orientation and crystal density. Therefore, in the past few decades, based on the basic principle of controlling the kinetics of intrinsic sensing reactions, people have synthesized various Fe2O3 nanostructures such as nanospindles, nanocubes, nanospheres, nanoflowers, nanotubes, etc. through a variety of strategies. In addition, by changing the intrinsic sensing reaction process, people have successfully adopted several effective strategies such as noble metal modification and other element doping, and composite with other materials to improve the sensing performance of Fe2O3. Among these methods, the combination of complex structures and chemical functions of composite materials is widely regarded as a simple and effective way to achieve high sensing performance. The advantages of large porosity, high specific surface area, large cavity volume and highly activated shell structure can effectively promote the adsorption or detachment of gas molecules from the material surface, help the migration of carriers inside the material, and thus improve the gas-sensing properties of the material.
[0004] In recent years, people have further realized that materials with specific nanostructures can exhibit unique properties or enhanced properties. Spurred by the discovery of carbon nanotubes and fullerenes, scientists have invested a lot of effort in developing nanomaterials with hollow interiors, such as hollow polyhedra and spheres, tubes, open cages, and frameworks, which has become an interesting research topic in the past two decades. Prussian blue (PB) is the first nanostructured material composed of Fe III Salt and [Fe II (CN)6] 4- The artificial coordination polymer (CP) obtained by coprecipitation in water has a face-centered cubic (fcc) unit cell, in which Fe III and FeII Alternately bridged by cyano ligands, iron can be replaced by other transition metal elements such as cobalt, nickel and manganese without destroying the basic fcc crystal structure, thus producing Prussian blue analogs (PBAs), which have fascinating physicochemical properties and a wide range of applications due to their unique structural characteristics, hollow structure, especially in electrochemical energy storage and conversion. In recent years, Prussian blue (PB) and its analogs (PBA) related nanomaterials have attracted extensive attention due to their low cost, convenient preparation, intrinsic open structure and adjustable composition.
[0005] With the progress of nanoscience and the in-depth understanding of hollow structures, non-spherical complex structures have been gradually separated from hollow porous structures as a unique and emerging structure. These structures have special performance advantages due to their additional advantages (such as adjustable chemical composition, fully open anisotropic hierarchical structure, etc.). The design and development of novel hierarchical metal oxide composites is expected to bring opportunities for the development of new gas sensors. Summary of the invention
[0006] The purpose of the present invention is to provide a Fe2O3 nanotube / ZnFe2O4 open nanocage composite material and its preparation method and application; in order to design and synthesize a novel hierarchical metal oxide composite material, the present invention uses a self-template epitaxial growth strategy combined with a heat treatment process to controllably prepare a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure, and systematically studies the gas-sensitive properties of the material, providing a new idea for constructing complex hierarchical nanomaterials, and providing a new choice for high-performance hydrogen sulfide sensitive materials.
[0007] The technical solution adopted by the present invention is as follows:
[0008] A method for preparing a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material, characterized in that the preparation method comprises the following steps:
[0009] (1) dissolving a zinc salt in dilute hydrochloric acid, adding an aqueous solution of potassium ferrocyanide thereto, stirring until the solution becomes a yellow suspension, standing at 10 to 95° C. for 2 to 36 hours, filtering, washing, and drying to obtain a zinc iron Prussian blue nanocube precursor material, and then dispersing the precursor material in deionized water, standing at 15 to 45° C. for aging for 24 to 120 hours, filtering, washing, and drying to obtain a zinc iron Prussian blue nanocage;
[0010] (2) Dispersing zinc-iron Prussian blue nanocages in deionized water, adding ferrous salt, stirring evenly, standing at 30-90°C for reaction for 3-24 hours, filtering, washing, and drying, and then heat treating at 280-520°C for 1-5 hours to obtain a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material.
[0011] In step (1), the zinc salt is one or more of zinc chloride, zinc sulfate, zinc acetate and zinc nitrate.
[0012] In step (1), the molar ratio of potassium ferrocyanide to zinc salt is 1:1.
[0013] In step (1), the concentration of the potassium ferrocyanide aqueous solution is 0.1-2.0 mol / L; the concentration of the zinc salt in dilute hydrochloric acid is 0.1-2.0 mol / L; and the concentration of the dilute hydrochloric acid is 0.1-1.2 mol / L.
[0014] In step (1), the standing condition is preferably 60-80° C. for 12-24 h; and the standing aging condition is preferably 20-30° C. for 72-96 h.
[0015] In step (2), the ferrous salt is one or more of ferrous sulfate, ammonium ferrous sulfate, ferrous chloride, and ferrous nitrate.
[0016] In step (2), the mass ratio of the zinc-iron Prussian blue nanocage to the ferrous salt is 1:0.75-2.5.
[0017] In step (2), the concentration of the zinc-iron Prussian blue nanocage in deionized water is 0.0015-0.02 g / mL.
[0018] In step (2), the static reaction condition is preferably 35-50° C. for 10-12 hours.
[0019] In step (2), the heat treatment condition is preferably 340-400° C. for 2-3 hours.
[0020] In step (2), the heating rate to the specified heat treatment temperature is 1 to 5°C / min, preferably 1 to 2°C / min.
[0021] The present invention also provides a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared by the preparation method.
[0022] The present invention also provides the application of the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material in a gas sensor, which has a highly sensitive response to hydrogen sulfide gas and good stability.
[0023] In the preparation method disclosed by the present invention, zinc iron Prussian blue nanocubes that are easy to prepare are used as precursors, and zinc iron Prussian blue nanocages are obtained through aging, and iron oxyhydroxide tubes / zinc iron Prussian blue analog nanocages are obtained through native growth, and Fe2O3 nanotubes / ZnFe2O4 open nanocage superstructure materials are obtained through heat treatment.
[0024] Some of the chemical reaction formulas involved in the reaction process are shown below:
[0025] 3Zn 2+ +2Fe(CN)6 3- →Zn3[Fe(CN)6]2 (1)
[0026] 4Fe 2+ +O2+4H + →4Fe 3+ +2H2O (2)
[0027] 2Fe 3+ +6Fe 2+ +3Zn3[Fe(CN)6]2→2Fe4[Fe(CN)6]3+9Zn 2+ (3)
[0028] 2Fe 2+ + O2 + 2H2O → 2FeOOH+ 4H + (4)
[0029] 2FeOOH→Fe2O3 + 2H2O (5)
[0030] The present invention adopts a self-templated epitaxial growth strategy combined with an annealing process to controllably prepare a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure, and systematically studies the gas-sensing properties of the material. The results show that the Fe2O3 nanotube / ZnFe2O4 open nanocage sensor has a relatively low operating temperature, a low detection limit, a fast response / recovery time, good reversibility and long-term stability, and its selectivity for H2S is significantly better than other reducing gases. The Fe2O3 nanotube / ZnFe2O4 open nanocage exhibits excellent sensitivity to H2S gas, which is mainly attributed to its hierarchical open structure with unobstructed gas diffusion channels, its heterogeneous structure that is conducive to interfacial charge transfer, and its abundant oxygen vacancies and adsorption catalytic reaction sites. The work of the present invention provides a new idea for the construction of complex hierarchical nanomaterials, and provides a new choice for the highly sensitive and highly selective detection of hydrogen sulfide gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1This is a SEM image of the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared in Example 1;
[0032] Figure 2 This is a SEM image of the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared in Example 2;
[0033] Figure 3 This is a SEM image of the zinc iron Prussian blue nanocube precursor prepared in Example 3;
[0034] Figure 4 This is the XRD pattern of the zinc iron Prussian blue nanocube precursor prepared in Example 3;
[0035] Figure 5 This is a SEM image of the zinc-iron Prussian blue nanocage prepared in Example 3;
[0036] Figure 6 This is the XRD pattern of the nanotube-modified zinc-iron Prussian blue nanocage prepared in Example 3;
[0037] Figure 7 This is a SEM image of the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared in Example 3;
[0038] Figure 8 The XRD pattern of the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared in Example 3;
[0039] Fig. 9 This is the EDS image of the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared in Example 3;
[0040] Fig.10 The BET diagram of the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared in Example 3;
[0041] Fig.11 This is a SEM image of the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared in Example 4;
[0042] Fig.12 This is a SEM image of the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared in Example 5;
[0043] Fig.13 This is a SEM image of the ZnFe2O4 open nanocage superstructure prepared in Comparative Example 1;
[0044] Fig.14This is the XRD pattern of the ZnFe2O4 open nanocage superstructure prepared in Comparative Example 1;
[0045] Fig.15 The response sensitivity of the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared in Example 3 and the ZnFe2O4 open nanocage sensor prepared in Comparative Example 1 to 10 ppm H2S and 100 ppm of different types of VOCs (including ethanol, isopropanol, acetone, benzene, toluene, n-butanol, methanol and ammonia, etc.) at an operating temperature of 140°C. DETAILED DESCRIPTION
[0046] The present invention is described in detail below with reference to the embodiments.
[0047] The reaction container used in step (2) in each embodiment is a beaker, and the mouth of the beaker is covered with plastic wrap during heating.
[0048] Example 1
[0049] A method for preparing a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material comprises the following steps:
[0050] (1) Potassium ferrocyanide is dissolved in deionized water to prepare 1000 mL of 0.1 M potassium ferrocyanide solution; zinc chloride is dissolved in 0.1 M dilute hydrochloric acid to prepare 1000 mL of 0.1 M zinc chloride-hydrochloric acid solution; the potassium ferrocyanide solution is added to the zinc chloride-hydrochloric acid solution under magnetic stirring at a speed of 150 rpm, and then stirring is continued at room temperature for 5 min to obtain a mixed suspension, which is allowed to stand at 10° C. for 36 h to obtain a yellow precipitate, and the yellow precipitate is filtered and washed to obtain a zinc iron Prussian blue nanocube precursor material, which is then dispersed in 50 mL of deionized water, allowed to stand at 15° C. for 120 h, and then fully washed with anhydrous ethanol and dried to obtain a zinc iron Prussian blue nanocage.
[0051] (2) Disperse 0.2 g of zinc iron Prussian blue nanocages in 15 mL of deionized water, add 0.15 g of ferrous chloride, stir vigorously for 5 min, and then transfer to a 90°C oven for reaction for 3 h. Wash the yellow precipitate thoroughly with deionized water and ethanol and dry it to obtain zinc iron Prussian blue nanocages modified with iron oxyhydroxide nanotubes.
[0052] (3) The obtained iron oxyhydroxide nanotube-modified zinc iron Prussian blue nanocage sample was transferred to a muffle furnace, heated to 280°C at a heating rate of 5°C / min and kept at this temperature for 5 h to obtain a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure. The SEM image is shown in Figure 1 shown.
[0053] Example 2
[0054] A method for preparing a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material comprises the following steps:
[0055] (1) Potassium ferrocyanide is dissolved in deionized water to prepare 1000 mL of 0.4 M potassium ferrocyanide solution; zinc sulfate is dissolved in 0.3 M dilute hydrochloric acid to prepare 1000 mL of 0.4 M zinc sulfate-hydrochloric acid solution; the potassium ferrocyanide solution is added to the zinc sulfate-hydrochloric acid solution under magnetic stirring at a speed of 160 rpm, and then stirring is continued at room temperature for 5 min to obtain a mixed suspension, which is allowed to stand at 30° C. for 30 h to obtain a yellow precipitate, and the yellow precipitate is filtered and washed to obtain a zinc iron Prussian blue nanocube precursor material, which is then dispersed in 90 mL of deionized water, allowed to stand at 25° C. for 100 h, and then fully washed with anhydrous ethanol and dried to obtain a zinc iron Prussian blue nanocage.
[0056] (2) Disperse 0.2 g of zinc iron Prussian blue nanocages in 50 mL of deionized water, add 0.25 g of ferrous sulfate, stir vigorously for 5 min, and then transfer to a 70°C oven for reaction for 5 h. Wash the yellow precipitate thoroughly with deionized water and ethanol and dry it to obtain zinc iron Prussian blue nanocages modified with iron oxyhydroxide nanotubes.
[0057] (3) The obtained iron oxyhydroxide nanotube-modified zinc iron Prussian blue nanocage sample was transferred to a muffle furnace, heated to 320°C at a heating rate of 4°C / min and kept at this temperature for 4 h to obtain a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure. The SEM image is shown in Figure 2 shown.
[0058] Example 3
[0059] A method for preparing a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material comprises the following steps:
[0060] (1) Potassium ferrocyanide was dissolved in deionized water to prepare 1000 mL of 0.9 M potassium ferrocyanide solution; zinc nitrate was dissolved in 0.7 M dilute hydrochloric acid to prepare 1000 mL of 0.9 M zinc nitrate-hydrochloric acid solution; the potassium ferrocyanide solution was added to the zinc nitrate-hydrochloric acid solution under magnetic stirring at a speed of 165 rpm, and then the stirring was continued at room temperature for 6 min to obtain a mixed suspension, which was allowed to stand at 60°C for 20 h to obtain a yellow precipitate, and the yellow precipitate was filtered and washed to obtain a zinc iron Prussian blue nanocube precursor material, which was then dispersed in 200 mL of deionized water, allowed to stand at 30°C for 72 h, and then fully washed with anhydrous ethanol and dried to obtain a zinc iron Prussian blue nanocage. Its SEM image is shown in the figure below. Figure 3As shown in the figure, it can be seen that it is a uniform nanocage; its XRD pattern is as follows Figure 4 As shown, the diffraction pattern proves that the prepared zinc-iron Prussian blue has a strong peak and high purity.
[0061] (2) Disperse 0.2g of zinc-iron Prussian blue nanocages in 80mL of deionized water, add 0.35g of ferrous sulfate, stir vigorously for 5min, and then transfer to a 55℃ oven for reaction for 18h. Wash the yellow precipitate thoroughly with deionized water and ethanol and dry it to obtain zinc-iron Prussian blue nanocages modified with oxyhydroxide nanotubes. The SEM image is shown in Figure 6 shown.
[0062] (3) The obtained iron oxyhydroxide nanotube-modified zinc iron Prussian blue nanocage sample was transferred to a muffle furnace, heated to 380°C at a heating rate of 3°C / min and kept at this temperature for 3 h to obtain a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure. The SEM image is shown in Figure 7 As shown in Figure 2, Fe2O3 nanotubes modified zinc iron Prussian blue nanocages. Its XRD Figure 8 As shown, it can be found that all diffraction peaks can be classified into two groups, which match Fe2O3 (JCPDS No.33-0664) and ZnFe2O4 (JCPDS No.22-1012) respectively, and there are no other impurity peaks; the product EDS diagram is shown in Fig. 9 As shown in the figure, it can be seen that the product contains zinc, iron and oxygen elements, and the silicon element comes from the silicon substrate. Fig.10 As shown, its specific surface area is 124.30m 2 g -1 The average pore size is 2.27 nm, indicating that it is a porous material with a large specific surface area.
[0063] Example 4
[0064] A method for preparing a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material comprises the following steps:
[0065] (1) Potassium ferrocyanide is dissolved in deionized water to prepare 1000 mL of a 1.5 M potassium ferrocyanide solution; zinc acetate is dissolved in 1.0 M dilute hydrochloric acid to prepare 1000 mL of a 1.5 M zinc acetate-hydrochloric acid solution; the potassium ferrocyanide solution is added to the zinc acetate-hydrochloric acid solution under magnetic stirring at a speed of 170 rpm, and then stirring is continued at room temperature for 8 min to obtain a mixed suspension, which is allowed to stand at 80° C. for 1 h to obtain a yellow precipitate, and the yellow precipitate is filtered and washed to obtain a zinc iron Prussian blue nanocube precursor material, which is then dispersed in 400 mL of deionized water, allowed to stand at 35° C. for 48 h, and then fully washed with anhydrous ethanol and dried to obtain a zinc iron Prussian blue nanocage.
[0066] (2) Disperse 0.2 g of zinc iron Prussian blue nanocages in 90 mL of deionized water, add 0.42 g of ferrous nitrate, stir vigorously for 5 min, and then transfer to an 80°C oven for reaction for 8 h. Wash the yellow precipitate thoroughly with deionized water and ethanol and dry it to obtain zinc iron Prussian blue nanocages modified with iron oxyhydroxide nanotubes.
[0067] (3) The obtained iron oxyhydroxide nanotube-modified zinc iron Prussian blue nanocage sample was transferred to a muffle furnace, heated to 450°C at a heating rate of 2°C / min and kept at this temperature for 2 h to obtain a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure. The SEM image is shown in Fig.11 Shown are zinc-iron Prussian blue nanocages modified with Fe2O3 nanotubes.
[0068] Example 5
[0069] A method for preparing a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material comprises the following steps:
[0070] (1) Potassium ferrocyanide is dissolved in deionized water to prepare 1000 mL of 2.0 M potassium ferrocyanide solution; zinc chloride is dissolved in 1.2 M dilute hydrochloric acid to prepare 1000 mL of 2.0 M zinc chloride-hydrochloric acid solution; the potassium ferrocyanide solution is added to the zinc chloride-hydrochloric acid solution under magnetic stirring at a speed of 180 rpm, and then stirring is continued at room temperature for 10 min to obtain a mixed suspension, which is allowed to stand at 95° C. for 2 h to obtain a yellow precipitate, and the yellow precipitate is filtered and washed to obtain a zinc iron Prussian blue nanocube precursor material, which is then dispersed in 500 mL of deionized water, allowed to stand at 45° C. for 24 h, and then fully washed with anhydrous ethanol and dried to obtain a zinc iron Prussian blue nanocage.
[0071] (2) Disperse 0.2 g of zinc iron Prussian blue nanocages in 120 mL of deionized water, add 0.5 g of ferrous sulfate, stir vigorously for 5 min, and then transfer to a 90°C oven for reaction for 3 h. Wash the yellow precipitate thoroughly with deionized water and ethanol and dry it to obtain zinc iron Prussian blue nanocages modified with iron oxyhydroxide nanotubes.
[0072] (3) The obtained zinc iron Prussian blue nanocage sample modified with oxyhydroxide nanotubes was transferred to a muffle furnace, heated to 520°C at a heating rate of 1°C / min and kept at this temperature for 1 h to obtain a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure. The SEM image is shown in Fig.12 Shown are zinc-iron Prussian blue nanocages modified with Fe2O3 nanotubes.
[0073] Comparative Example 1
[0074] A method for preparing a ZnFe2O4 open nanocage superstructure composite material comprises the following steps:
[0075] (1) Potassium ferrocyanide was dissolved in deionized water to prepare 1000 mL of 0.9 M potassium ferrocyanide solution; zinc nitrate was dissolved in 0.7 M dilute hydrochloric acid to prepare 1000 mL of 0.9 M zinc nitrate-hydrochloric acid solution; the potassium ferrocyanide solution was added to the zinc nitrate-hydrochloric acid solution under magnetic stirring at a speed of 165 rpm, and then stirred at room temperature for 6 min to obtain a mixed suspension, which was allowed to stand at 60° C. for 20 h to obtain a yellow precipitate, which was filtered and washed. The obtained zinc iron Prussian blue nanocubes were dispersed in 200 mL of deionized water, allowed to stand at 30° C. for 72 h, and then fully washed with anhydrous ethanol and dried to obtain a zinc iron Prussian blue nanocage.
[0076] (2) The obtained zinc-iron Prussian blue nanocage sample was transferred to a muffle furnace and heat treated at 380°C for 3 h at a heating rate of 3°C / min to obtain a ZnFe2O4 open nanocage superstructure. The SEM image is shown in Fig.13 As shown in Figure 2, the product morphology is nanocage-like. Fig.14 As shown, all diffraction peaks are consistent with ZnFe2O4 (JCPDS No.22-1012) and there are no other impurity peaks.
[0077] Application Example 1
[0078] Application of Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite in gas sensor
[0079] The Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared in Example 3 and the ZnFe2O4 open nanocage prepared in Comparative Example 1 were dispersed in anhydrous ethanol respectively, and then evenly coated on a ceramic tube with electrodes to make a gas sensor, dried at 50°C for 2 hours, and then heat treated at 200°C for 2 hours. Then, a small nickel-chromium alloy coil was placed in the tube as a heater to provide the sensor with an operating temperature. The sensor was aged at 300°C for 48 hours, and then different volatile organic gases were tested at the operating temperature. The specific test operation steps are: use a syringe to inject a certain amount of organic vapor into the sensor test box, wait for about 2 minutes, and then introduce dry air into the test box after the sensor output response value stabilizes. The sensor output response gradually recovers, and the output response value of the sensor in dry air and with the target gas is tested and recorded using an electrochemical workstation and a computer. The sensor's sensitivity to gas response is defined as S=R a / R g (reducing gas), R ais the resistance of the sensor in dry air, R g is the resistance of the sensor in the test gas.
[0080] Fig.15 The response sensitivity of the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared in Example 3 and the ZnFe2O4 open nanocage sensor prepared in Comparative Example 1 to 10ppm H2S and 100ppm different types of VOCs (including ethanol, isopropanol, acetone, benzene, toluene, n-butanol, methanol and ammonia, etc.) at an operating temperature of 140°C. The study shows that the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared in Example 3 has a good sensitive response to common toxic and harmful organic gases in the air, and its sensitivity is significantly better than that of the ZnFe2O4 open nanocage material, such as Fig.15 As shown in the figure, it can be seen that the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared by this method shows good selectivity for hydrogen sulfide compared with different types of VOCs (including ethanol, isopropanol, acetone, benzene, toluene, n-butanol, methanol and ammonia, etc.), so it is appropriate to choose Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure as a sensitive material for H2S gas.
[0081] The detailed description of a Fe2O3 nanotube / zinc ferrite open nanocage superstructure composite material and its preparation method and application with reference to the above-mentioned embodiment is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material, characterized in that: The preparation method comprises the following steps: (1) dissolving a zinc salt in dilute hydrochloric acid, adding an aqueous solution of potassium ferrocyanide thereto, stirring until the solution becomes a yellow suspension, standing at 10 to 95° C. for 2 to 36 hours, filtering, washing, and drying to obtain a zinc iron Prussian blue nanocube precursor material, and then dispersing the precursor material in deionized water, standing at 15 to 45° C. for aging for 24 to 120 hours, filtering, washing, and drying to obtain a zinc iron Prussian blue nanocage; (2) Dispersing zinc-iron Prussian blue nanocages in deionized water, adding ferrous salt, stirring evenly, standing at 30-90°C for reaction for 3-24 hours, filtering, washing, and drying, and then heat treating at 280-520°C for 1-5 hours to obtain a Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material.
2. The preparation method according to claim 1, characterized in that: In step (1), the zinc salt is one or more of zinc chloride, zinc sulfate, zinc acetate and zinc nitrate.
3. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of potassium ferrocyanide to zinc salt is 1:
1.
4. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the potassium ferrocyanide aqueous solution is 0.1 to 2.0 mol / L; the concentration of the zinc salt in dilute hydrochloric acid is 0.1 to 2.0 mol / L; The concentration of the dilute hydrochloric acid is 0.1-1.2 mol / L.
5. The preparation method according to claim 1, characterized in that: In step (2), the ferrous salt is one of ferrous sulfate, ferrous chloride and ferrous nitrate.
6. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the zinc-iron Prussian blue nanocage to the ferrous salt is 1:0.75-2.
5.
7. The preparation method according to claim 1, characterized in that: In step (2), the concentration of the zinc-iron Prussian blue nanocage in deionized water is 0.0015-0.02 g / mL.
8. The preparation method according to claim 1, characterized in that: In step (2), the heating rate to the specified heat treatment temperature is 1 to 5°C / min.
9. The Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the Fe2O3 nanotube / ZnFe2O4 open nanocage superstructure composite material as claimed in claim 9 in a gas sensor.
Citation Information
Patent Citations
Preparation method and application of pseudo-cubic ferric oxide nanocage with multilevel structure
CN108285175A
Iron oxide material with hollow cube structure as well as preparation method and application of iron oxide material
CN114735755A
Preparation method of hollow nanocage Prussian blue MOFs
CN117509678A
Ferrate nanocage superstructure material as well as preparation method and application thereof
CN119750652A